Konsep Diri Remaja Yang Mengalami Kegagalan Hubungan Interpersonal - Ayu Ningsih (Jurnal Psikologi Terapan, 2019)
Self-concept of adolescents who experience failure of interpersonal relationships is characterized by 3 (three) aspects, namely having a low self-concept, difficulty making new relationships with others and often thinking pessimistically. As well as the self-concept of adolescents can also be seen from developmental tasks that are the same age as the subject, which tends to have several developmental tasks that are not in accordance with the current subject's self, so that this can have an impact on negative self-concept So that previous research with current research has a significant difference, namely previous research says the strength of the relationship between self-concept and self-confidence with interpersonal communication skills is only 23.7%. This study aims to see the self-concept of adolescents who experience failure in interpersonal relationships.